Factors critical to the success of six-sigma quality program and their influence on performance indicators in some of Lebanese hospitals - Assrar Sabry (Arab Economic and Business Journal, 2014)
Medical literature reports that Six-Sigma was applied at specific healthcare organizations. However, there is a lack of studies that investigate the broader status of Six-Sigma in Lebanese healthcare systems. The purpose of this paper is to explore the realities of factors critical (CSFs) to the success of a Six-Sigma quality program to identify the nature of the quality program implemented in some of Lebanese hospitals in Beirut. It also examines the impact of (CSFs) of a Six-Sigma quality program and its influence on performance indicators.In order to achieve the objectives of the study, two questionnaires were used; ANOVA, Eta Squared, Pearson Correlations were used to analyse the data collected from a sample of 101 respondents. Three hypotheses, (H1), (H2) and (H3), were tested and partially accepted based on the results found.The rest of the paper is organized as follows: First, an overview on the relevant literature reviews with respect to the identified Six-Sigma factors. After that, the methodology and the data analysis of the results are presented. The end of this paper is concluded with the discussion and suggestions for further research.
Keywords: 650; Six-Sigma quality program; Critical success factors; Key performance indicators; Hospitals; CSFs; KPIs